Systematic Literature Review: How Financial Literacy, Trust and Firm Reputation Affect Investment Decision - Carolina, Sinta; Iqbal, Mohammad; Darmawan, Ari (FIA UB, 2025)
The urge for investment has increased these past ten years. The rise of investment awareness is side by side with Indonesia’s financial literacy awareness in 2019. After the pandemic, people became more aware of saving and investing. On the other hand, investment preferences have become a particular topic. Several factors could affect investment preferences, such as trust and firm reputation. Based on this condition, this research aims to understand how financial literacy, trust, and firm reputation affect individual investment behaviour based on previous studies. Through the Systematic Literature Review (SLR) method and PRISMA protocol, this research used 49 articles from Google Scholar and Science Direct. Results show that financial literacy and trust affect investment decisions. Reputation has a slightly different effect and indirect correlation on individual investing behaviour. This research provides recommendations for future studies concerned with the topic and method.